1995
DOI: 10.1038/bjc.1995.364
|View full text |Cite
|
Sign up to set email alerts
|

Review of survival analyses published in cancer journals

Abstract: Summary Survival analysis has found widespread applications in medicine in the last 10-15 years. However, there has been no published review of the use and presentation of survival analyses. We have carried out a systematic review of the research papers published between October and December 1991 in five clinical oncology journals. A total of 132 papers were reviewed. We looked at several aspects of study design, data handling, analysis and presentation of the results. We found that almost half of the papers d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
301
0
5

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(310 citation statements)
references
References 46 publications
4
301
0
5
Order By: Relevance
“…Although randomized controlled trials are considered the highest level of evidence, registries have recently gained recognition as credible data sources [13,19,32,37]. However, our assessment of the quality of reporting of these studies identified deficiencies similar to those previously identified in a review of survival analyses [3]. For example, only 43% of studies included in our review reported the number of patients that were at risk of revision at each followup time, estimates of precision (such as SEs or CIs), or the statistical software used.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although randomized controlled trials are considered the highest level of evidence, registries have recently gained recognition as credible data sources [13,19,32,37]. However, our assessment of the quality of reporting of these studies identified deficiencies similar to those previously identified in a review of survival analyses [3]. For example, only 43% of studies included in our review reported the number of patients that were at risk of revision at each followup time, estimates of precision (such as SEs or CIs), or the statistical software used.…”
Section: Discussionmentioning
confidence: 88%
“…Because no validated tool is available to assist in examining the quality of reporting specifically for survival analysis studies, we developed criteria based on recommendations and guidelines for reporting these types of analyses [1,3,9,12,34,35,38]. Nine criteria were assessed independently by the same two reviewers (SL, TW), who asked: (1) Was the number of patients at risk presented at each followup time?…”
Section: Methodsmentioning
confidence: 99%
“…Initial ideas for key elements to be addressed in the guidelines were assembled from literature citing empirical evidence of inadequate reporting or problematic analysis methods (Hilsenbeck et al, 1992;Altman et al, 1994Altman et al, , 1995Simon and Altman, 1994) based on published reviews of tumour marker studies. Ideas were also generated by reviewing similar reporting guidelines that have been produced for other types of medical research studies (CONSORT, QUOROM, MOOSE, STARD) (Moher et al, 1999Stroup et al, 2000;Bossuyt et al, 2003a).…”
Section: Methodsmentioning
confidence: 99%
“…Statistical problems are commonplace. These problems include underpowered studies or overly optimistic reporting of effect sizes and significance levels due to multiple testing, subset analyses, and cutpoint optimisation (Altman et al, 1995).…”
mentioning
confidence: 99%
“…Cutoff points are frequently used to dichotomise continuous markers and define groups, while different outcomes, adjustment factors and groups of patients are common features across prognostic studies. Inadequate reporting and presentation of survival data has been shown to be a concern in the cancer literature (Altman et al, 1995).…”
Section: Generalisations To Other Prognostic Markersmentioning
confidence: 99%